The influence of organisational safety climate on group safety outcomes: The mediation role of supervisor safety communication and monitoring - Kandola, R.; Curcuruto, M.; Griffin, Mark; Morgan, J. (2019)
Safety climate is an important leading indicator of safety performance and reflects the priority of safety within industrial operations. Previous research has identified safety climate as a multilevel and multidimensional construct, which involves the interaction of multiple social agents at various levels of organisations, including managers, supervisors, and work-groups. The present paper tests the mediation role of two types of safety supervision styles, safety monitoring supervision (SMS) and safety communication supervision (SCS), on the relationship between organisational safety climate (OSC) and relevant group outcomes for safety management. Results found that on one hand, OSC affects performative safety management dimensions of work-groups, through the influence of SMS. On the other hand, SCS seems to exercise a mediation role of the effects of OSC on work dimensions supporting psychological health and the quality of the psychosocial environment.